2008
DOI: 10.1007/s00787-007-0668-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial conditions and suicidal behavior in pregnant teenagers

Abstract: The PT case group exhibited a psychosocial profile whose characteristics clearly differentiate this group from the NPT control group. Preventive mental health care is needed to help PT because their behavioral pattern exposes them to high risk for suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…Additional evidence of psychological distress among Brazilian pregnant adolescents has been reported by Freitas et al [6], who conducted a case-controlled study to compare the psychosocial profile and suicidal behaviour of 110 pregnant and 110 non-pregnant adolescents. The findings indicated that adolescent pregnancies were associated with: substance use, low level of social support, depression, traumatic life events and other psychosocial difficulties.…”
Section: Introductionmentioning
confidence: 88%
“…Additional evidence of psychological distress among Brazilian pregnant adolescents has been reported by Freitas et al [6], who conducted a case-controlled study to compare the psychosocial profile and suicidal behaviour of 110 pregnant and 110 non-pregnant adolescents. The findings indicated that adolescent pregnancies were associated with: substance use, low level of social support, depression, traumatic life events and other psychosocial difficulties.…”
Section: Introductionmentioning
confidence: 88%
“…Adolescent pregnancy has been associated with multiple risk factors, including depression, substance use, smoking, and violence (Freitas et al 2008; DuRant et al 1996; Simantov et al 2000). A case–control study in Brazil, comparing 110 pregnant teens with 110 nonpregnant teens that were recipients of medical assistance through a prenatal program, found that the pregnant teens reported significantly higher levels of previous alcohol, illicit drug and tobacco use, a higher frequency of physical and emotional abuse, and higher levels of depression and anxiety as compared with nonpregnant teens; however, the study did not assess the relative contributions of these variables on depression severity (Freitas et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A case–control study in Brazil, comparing 110 pregnant teens with 110 nonpregnant teens that were recipients of medical assistance through a prenatal program, found that the pregnant teens reported significantly higher levels of previous alcohol, illicit drug and tobacco use, a higher frequency of physical and emotional abuse, and higher levels of depression and anxiety as compared with nonpregnant teens; however, the study did not assess the relative contributions of these variables on depression severity (Freitas et al 2008). A prospective study of 1,888 pregnant women (mean age=30 years old; 71 % Caucasian) identified factors that were significantly associated with antenatal depressive disorders, including psychosocial stress, chronic medical conditions, ethnicity, young age, and intimate partner violence (sexual and/or physical violence), which was the strongest independent predictor of major depression with an odds ratio of 3.45 (Melville et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…72 Actions to prevent suicide can also be started in the general hospital, in at least two groups of individuals: in those who, after being assessed as outpatients or hospitalized patients, a mental disorder is detected and among those who are seen due to a suicide attempt. 35,73,74 It is estimated that the suicide risk in hospitalized patients is three times that of the general population. 75 The majority of those who commit suicide during hospitalization suffer from chronic or terminal diseases, or yet of painful and debilitating conditions.…”
Section: Other Developmental Factorsmentioning
confidence: 99%